O diálogo entre teoria e prática : uma formação continuada de professores de ciências em serviço utilizando o Diagrama V - Rabbi, Michel Adriano (2016)
Initially, a review of literature about the formation of the teachers in science was made, once were listed problematics, were identified objectives, theoric references and categorized the conclusions of the selected articles. This revision motived the following question of search: how to build with science teachers in collective meetings, reflections about their practices in the search for autonomy, of form to deal with their resistance and tension to develop strategies that they could effectively use in the classroom? In this sense, It was developed a curse of formation to teachers, with the objective of to analyze a collective process of continuous formation of teachers in service, where they could reflect in their practices, favoring the dialogue between theory and practice in the construction and development of the pedagogical act. During the process of formation, was used the Diagram V (described detailed in the text) not how a methodology, but how a auxiliary tool in the educatives processes.The continue formation involved five science teachers of municipal schools of Cachoeiro de Itapemirim - ES, they meet in the presence and participation of the researcher, discussing and building the curse in a perspective formative and collaborative. The presential meetings happened during one semester, intercalate with the realization home planning activities and activities with students at school. To collect data, all meetings were recorded and speeches of teachers transcribed. Beyond that, they collected the Diagrams V produced by teachers and by students. The impressions of students in relation to the activities were collected too, through spontaneous speeches of the same and produced texts. These data were analyzed qualitatively through of analysis of content and watching the Critical Movements Reflexive of the search-action,selected as option theoric-methodologic in the context of the continued formation of teachers. To reflect collectively , with a construction of Diagrams V with the students it was a pratic assumed by teachers. They insert themselves in a way which could to be researchers of their own practice, they might to know a new strategy of teaching and to recognize, the validity of this proposal in their contexts in classroom and their personal potential to elaborate and develop innovations in the education, where the concept of Critical Movement Reflexive was getting significant presence in that cycles in the proportion in that they were advancing. And finally, beyond to proposing a concept Autonomy Teacher , in the context of the Formation de Teachers, also suggest an adaptation and expansion of Diagram V Gowin (1981). Now we would have the Diagram M, alluding to Critical Movement Reflexive theoretically investigated and discussed in practice of this work of doctorate.